Benzoin gardens in North Sumatra, Indonesia: effects of management on tree diversity - García Fernandez, C.; Casado, M.A.; Ruíz Pérez, M. (2003)
In recent years, research on tropical forest conservation has increasingly focused on traditional management systems as a means of achieving a balance between conservation and development. Styrax paralleloneurun, a forest-canopy tree species that produces benzoin, an aromatic resin, is cultivated in such a system. This study is an attempt to determine the impact of benzoin garden management on forest structure, species composition, and diversity. Forty-five gardens were chosen for study in two Northern Sumatra villages, where data on management practices and ecological structure were gathered. Ecological information was also collected from abandoned benzoin garden and primary forest areas for purposes of comparison. Although benzoin management requires that competing vegetation be thinned, these activities are not intensive, allowing species that coppice to remain in the garden and thereby reducing the effects of competitive exclusion mechanisms on species composition. Tree species diversity in abandoned gardens was similar to that in primary forest, but endemic species and species characteristic of mature habitats were less common. Traditional benzoin garden management represents only a low-intensity disturbance and maintains an ecological structure that allows effective accumulation of forest species over the long term.